Effect of mound height and cassava cultivar on cassava performance under a fluctuating water table - Mohamoud, Y. (Elsevier, 1994)
Field experiments were conducted at Ibadan and Bida in Nigeria, west Africa, to investigate the effect of mound height and cassava cultivar on cassava performance (tuber yield, top yield, tuber length, and plant height). In the Ibadan site, where the soil surface become waterlogged before cassava harvesting, cassava tuber yield, top yield, and tuber length among mounds were statistically different. But, between cultivars only tuber yield and tuber length were significantly different. In the Bida site, where the water table was deep only top yields among mounds were significantly different while between cultivars tuber and top yield were significantly different. The results of this study indicate that the 30 cm high mound, at both sites, gave the least performance in tuber yield, top yield, tuber length and plant height. However, in both sites, cassava performance among the 60, 90 and 120 cm high mounds were not significantly different. Also, in Ibadan site, all the 30 cm and some 60 cm high mounds showed symptoms of chlorosis and stunted vegetative growth as well as tuber rot. No such symptoms were observed at the Bida site.